The relation between bone demineralization, physical activity and anthropometric standards - Camara, Milena Barbosa (2017)
This paper aimed to verify the correlation between bone mineral density and the level of physical activity, as well as the food intake and the anthropometric parameters. It intended to analyse the bone mineral density (BMD) of menopausal women through the bone densitometry test (DO) in the lumbar region (L1 to L4), femoral neck and total femur, and also use Bouchard’s self-recall of daily activities; employing the food record from Buker and Stuart to dose and quantify the daily intake of calcium and vitamin D. The data were analysed via Kolmogorov-Smirnov’s test, and default value of α = 0.05 was set to compare the BMD averages. It was observed that one hundred percent of the assessed individuals had a BMD level below the average fixed by WHO: 14.4% with osteopenia and 85.6% with osteoporosis; a lower BMD in the femoral area (0.721g) and the biggest loss among the sedentary ones (0.698g). It was noticed that there was a correlation between the physical activities and the BMD only when associated with anthropometric standards and the daily ingestion of vitamin D.